POISONS IMPLICATED IN HOMICIDAL, SUICIDAL AND ACCIDENTAL CASES IN NORTH-WEST PAKISTAN - Jan, Adil; Khan, Muhammad Jaffar; Khan, Muhammad Tariq Humayun; Khan, Muhammad Tariq Masood; Fatima, Sadia (Journal of Ayub Medical College Abbottabad, 2016)
Background: Pakistan has one of the highest prevalence of poisoning in the world. However, limited data exist on the frequency of poisons implicated in homicidal, suicidal, and accidental cases in North-West Pakistan (Khyber Pakhtunkhwa). Methods: This retrospective study of 353 cases and biological specimens of poisoning received at the department of Forensic medicine and toxicology, Khyber Medical College Peshawar from 13 districts of Khyber Pakhtunkhwa. Frequency of poisoning was assessed by testing each specimen for 17 different poisons. Results: Of all the specimens, 250 (70.8%) specimens tested positive and the rest didn’t show any indication of poisoning (n=103, 29.2%). The most frequent poisons detected were benzodiazepines (total n=75), organophosphates (total n=58), phencyclidine (total n=30) and morphine (total n=23). Gender had a significant association with benzodiazepines (p=0.011), tricyclic antidepressants (p=0.001), and organophosphates (p<0.001). Organophosphates were the most common cause of poisoning in females while benzodiazepines were the most common cause of poisoning in males. Conclusion: Poisoning by benzodiazepines, organophosphates and phencyclidine are the most common causes of intoxication in population of Khyber Pakhtunkhwa. Source of poisoning varies with gender for organophosphates, benzodiazepines and tricyclic antidepressants. Keyword: Poisoning, Organophosphates, Benzodiazapines, phencyclidine, Morphine, Pakistan